Предмет: Алгебра, автор: DimaSavva22

мне бы решить по фасту

Приложения:

Ответы

Автор ответа: NNNLLL54
0
left (sqrt{ab}- frac{ab}{a+sqrt{ab}} right ): frac{a^2b}{a-b} =left ( frac{sqrt{ab}cdot (a+sqrt{ab})-ab}{a+sqrt{ab}} right ): frac{a^2b}{(sqrt{a}-sqrt{b})(sqrt{a}+sqrt{b})} =\\= frac{asqrt{ab}+ab-ab}{sqrt{a}cdot (sqrt{a}+sqrt{b})} cdot   frac{(sqrt{a}-sqrt{b})(sqrt{a}+sqrt{b})}{a^2b} = frac{asqrt{a}cdot sqrt{b}}{sqrt{a}} cdot  frac{sqrt{a}-sqrt{b}}{a^2b} =\\= frac{sqrt{a}-sqrt{b}}{asqrt{b}}
Похожие вопросы
Предмет: Алгебра, автор: boschkovskanasta
Предмет: Алгебра, автор: igrypley3